Effects of pentoxifylline on inflammatory markers and blood pressure: a systematic review and meta-analysis of randomized controlled trials. Issue 12 (December 2016) - Brie, Daniel; Sahebkar, Amirhossein; Penson, Peter E.; Dinca, Madalina; Ursoniu, Sorin; Serban, Maria-Corina; Zanchetti, Alberto; Howard, George; Ahmed, Ali; Aronow, Wilbert S.; Muntner, Paul; Lip, Gregory Y.H.; et al.
Abstract : Introduction: Pentoxifylline is a xanthine derivative with potential cardiovascular benefits. Aim: To evaluate the impact of pentoxifylline on blood pressure (BP) and plasma TNF-α, C-reactive protein (CRP) and IL-6 through a systematic review and meta-analysis of randomized controlled trials. Methods: The protocol was registered (PROSPERO: CRD42016035988). The search included PUBMED, ProQuest, Scopus and EMBASE until 1 September 2015 to identify trials reporting BP or inflammatory markers during pentoxifylline therapy. Quantitative data synthesis was performed using a random-effects model, with weighted mean difference (WDF) and 95% confidence intervals (CIs) as summary statistics. Results: Fifteen studies (16 treatment arms) were found to be eligible for inclusion. Meta-analysis did not suggest any effect of pentoxifylline on either SBP or DBP. Pentoxifylline treatment was associated with a significant reduction in plasma concentrations of TNF-α (WDF: −1.03 pg/ml, 95% CI: −1.54, −0.51; P  < 0.001, 11 treatment arms) and CRP (WDF: −1.39 mg/l, 95% CI: −2.68, −0.10; P  =   0.034, five treatment arms). No alteration in plasma IL-6 concentration was observed. The impact of pentoxifylline on plasma TNF-α levels was found to be positively associated with treatment duration (slope: 0.031; 95% CI: 0.004, 0.057; P  = 0.023) but independent of pentoxifylline dose (slope: −0.0003; 95% CI: −0.002, 0.001; P  = 0.687). Conclusion: Pentoxifylline did not alter BP or plasma IL-6 concentration, but significantly reduced circulating TNF-α and CRP concentrations.